Evaluation of sCD163 and sTWEAK in patients with stable peripheral arterial disease and association with disease severity as well as long-term mortality. (January 2021) - Mrak, Daniel; Zierfuss, Bernhard; Höbaus, Clemens; Herz, Carsten Thilo; Pesau, Gerfried; Schernthaner, Gerit-Holger
Abstract: Background and aims: The TNF-superfamily member sTWEAK and its scavenger receptor sCD163 are potentially involved in pathophysiological processes of atherosclerosis. In patients with peripheral arterial disease, previous research has shown that sTWEAK and the sCD163/sTWEAK ratio were independently associated with long term all-cause and cardiovascular survival. Since previous investigations emphasized on symptomatic peripheral arterial disease including critical limb ischemia, this study evaluates sTWEAK and sCD163 in a cohort of stable peripheral arterial disease including asymptomatic (Fontaine stage I) and intermittent claudication (Fontaine stage II) patients. Methods: sTWEAK concentrations of 354 patients were measured using a commercially available ELISA kit. sCD163 was quantified using a multiplex bead assay. Cox proportional hazards regression was used to assess outcome after a seven-year follow-up. Hazard ratios are given as interquartile range. Results: Patients with intermittent claudication exhibited increased sCD163 levels in comparison to asymptomatic patients ( p  = 0.002). However, sTWEAK was not related to peripheral arterial disease severity ( p  = 0.740). A multivariable Cox-proportional hazard models including sTWEAK and cardiovascular risk factors (age, HbA1c, CRP, LDL-C, BMI, eGFR) revealed an inverse association with all-cause mortality (HR 0.775 (95% CI 0.623–0.965) and cardiovascular mortality (HR 0.710 (95% CI 0.534–0.944)). Further multivariable models including sCD163 or the sCD163/sTWEAK ratio and cardiovascular risk factors showed no association with mortality. Conclusions: This study highlights the use of sCD163 as a novel biomarker for PAD severity and supports sTWEAK as an independent predictor of all-cause and cardiovascular mortality even in stable peripheral arterial disease. Graphical abstract: Image 1 Highlights: sCD163 is significantly elevated in symptomatic  vs asymptomatic peripheral arterial disease. sTWEAK showed an inverse association with all-cause and cardiovascular mortality in stable peripheral arterial disease. Adding sTWEAK to the Cox-proportional hazards model of all-cause mortality resulted in a net reclassification improvement.